Dysmenorrhoea and its effects on school activities among adolescent girls in a rural school in Selangor, Malaysia - I Liliwati; LKM Verna; O Khairani (Penerbit UKM, 2007)
The objective of this study is to determine the prevalence of dysmenorrhoea, its associated factors and its effects on school activities among adolescent girls in a secondary school in a rural district of Selangor, Malaysia. This is a cross-sectional study conducted in a public secondary school. A stratified random sampling of 300 female students (12 to 17 years old) from Form one to Form five classes were selected. A self-administered questionnaire consisting of 20-items was used to collect sociodemographic and menstrual data. Pain intensity for dysmenorrhoea was measured by numerical rating scale. The prevalence of dysmenorrhoea was 62.3%. It was significantly higher in the middle adolescence (15 to 17 years old) age group (p=0.003), girls with regular menstrual cycle (p=0.007) and a positive family history (p<0.05). There was no significant association with mean age of menarche and duration of menstruation. The number of school and class absences increased with increasing severity of dysmenorrhoea (p<0.05). The mean pain score was significantly higher in girls who reported to be unable to participate in sports (p=0.008) and with poor concentration in class (p<0.05). Dysmenorrhoea among the adolescent girls was common in this rural school. It had significant negative impact in their school performance and activities